1994
DOI: 10.3892/or_00000046
|View full text |Cite
|
Sign up to set email alerts
|

Skp2, p27kip1 and EGFR assessment in head and neck squamous cell carcinoma: Prognostic implications

Abstract: Abstract. EGFR, p27kip1 and Skp2, have been implicated in human cancer development. We have studied these molecules in a search for molecular markers that may have prognostic value in head and neck squamous cell carcinomas (HNSCC). Tissue samples of 62 patients were collected and immunohistochemical analysis was carried out for p27 kip1 , Skp2 and EGFR protein evaluation. Western blot analysis of p27 kip1 was performed. The p27 kip1 expression is frequently down-regulated in HNSCC (44.4%, 20/45 cases). The imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…colon cancer, ovarian cancer, Barrett‐associated adenocarcinoma and malignant peripheral nerve sheath tumour . Two studies on OSCC have reported a diffuse cytoplasmic staining in occasional tumour cells, although nuclear staining was predominant . However, scoring of this cytoplasmic p27 staining and correlation with survival were not performed by them.…”
Section: Discussionmentioning
confidence: 99%
“…colon cancer, ovarian cancer, Barrett‐associated adenocarcinoma and malignant peripheral nerve sheath tumour . Two studies on OSCC have reported a diffuse cytoplasmic staining in occasional tumour cells, although nuclear staining was predominant . However, scoring of this cytoplasmic p27 staining and correlation with survival were not performed by them.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important element emerges from the present data: patients who presented Skp2 values greater than 20% deceased within 3 years from surgery. The previous studies demonstrated a strong correlation between Skp2 overexpression, metastatic capability of the tumour and a decrease in overall survival (Harada et al , 2005a,b; Carracedo et al , 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The cyclin/CDK complexes are activated by means of phosphorylation which is carried out by CDK activating kinases (CAK) and that, in turn, are negatively regulated by diverse CDK inhibitors (CDIs) (Toyoshima and Hunter, 1994; Sherr, 1996). The expression of cyclins, CDKs and CDIs, which is finely coordinated in non‐pathological conditions, is often deregulated in tumours (Carracedo et al , 2008). The role played by p27 is that of a negative regulator of G0/G1 phase and a low expression of this protein is associated with disease progression (Hunter and Pines, 1994; Toyoshima and Hunter, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…W dostępnym piśmiennictwie można znaleźć prace, w których autorzy wskazują na rolę wielu biomarkerów związanych m.in. z regulacją cyklu komórkowego, p27kip1, Skp2, Ki67, jako potencjalnych wskaźników inwazyjności zmian, determinujących rokowanie oraz wybór właściwego postępowania terapeutycznego [1][2][3][4][5][6]. Wśród publikacji dotyczących tego tematu można jednak wskazać prace, które nie potwierdzają roli wspomnianych wykładników jako niezależnych wskaźników agresywności wzrostu nowotworu i czynników o znaczeniu prognostycznym [7][8][9].…”
Section: Wstępunclassified